Demographic Factors and Disease History Associated with Dementia among Elderly in Nursing Homes - Lisna Anisa Fitriana; Nazhifa Ufamy; Kusnandar Anggadiredja; Linda Amalia; Setiawan Setiawan; I Ketut Adnyana (Jurnal Keperawatan Padjadjaran, 2020)
Dementia is increasing in the world which is a major cause of disability and dependence in the elderly. This causes the elderly can not do their daily activities so often live in a nursing home. It is important to know the factors associated with dementia to prevent and treat dementia with appropriate interventions. The objective of this study was to identify the demographic factors and disease history associated with dementia among elderly in nursing homes. The research method was cross sectional study. Sample were recruited from three nursing homes located in Bandung and Garut using purposive sampling technique for a-3 month period (n=163). Data were collected using questionnaire consisting of demographic data, disease history, and MMSE (Mini Mental State Examination). The analysis of data was performed using chi-square test, fisher test, and logistic regression analysis. In term of its association with dementia, low education had the higher odd ratio (OR: 5.90, 95% CI: 2.02-17.20, p=0.001) than unmarried status (OR: 4.78, 95% CI: 1.23-18.52, p=0.024) and stroke (OR: 0.23, 95% CI: 0.06-0.88, p=0.032). However, diabetes mellitus was identified as confounding variable (OR: 0.10, 95%CI: 0.01-1.01, p=0.051). In conclusion, low education, unmarried status, stroke, and diabetes mellitus were predictor factors of dementia among elderly in nursing homes. It is recommended to include effective treatment could be in the form of health education about management of stroke and diabetes, physical activity, improvement of nutritional adequate, and social activities to prevent loneliness.